Synthesis of novel N-(p-toluenesulfonyl)aminophosphonates and evaluation of their biological properties. (3rd July 2018) - Karpowicz, Rafał; Lewkowski, Jarosław; Stasiak, Małgorzata; Czopor, Aleksandra; Tokarz, Paulina; Król, Adrianna; Rogacz, Diana; Rychter, Piotr
GRAPHICAL ABSTRACT: ABSTRACT: The synthesis of a series of N -sulfonylaminophosphonates2aA-2dC and evaluation of their cytotoxicity and ecotoxicity is described. N -sulfonylaminophsophonates2aA-2dC were obtained by addition of dialkyl phosphites to azomethine bonds of sulfonimines1a-d in dichloromethane, and the reaction was mediated by potassium carbonate. Sulfonimines1a-d were synthesized by direct condensation of selected aldehydes with p- toluenesulfonamide catalyzed by titanium(IV) ethoxide. The cytotoxicity of compounds2aB-2cB, 2aC-2cC, 2bA and2dA against normal primary human lymphocytes, non-small cell lung cancer cells A549, promyelocytic leukemia cells HL-60 and glioblastoma astrocytoma cells U87 was found to be very low. The phytotoxicity of2dC against monocotyledonous oat ( A. sativa ) and dicotyledonous radish ( R. sativus ) was measured and the compound was found to be practically not toxic for two model plants. Lack of toxicity for marine bacteria A. fischeri has been also detected. However, the compound2dC was found to be significantly toxic for freshwater, European crustaceans H. incongruens (ostracods).